City deals and skills : how have City and Local Growth Deals supported the development of employment and skills policies that reflect local demand? /: how have City and Local Growth Deals supported the development of employment and skills policies that reflect local demand?. (July 2015) - Clayton, Naomi; McGough, Louise; Centre for Cities,
No abstract available